China connects the world what behind the belt and road initiative - Wang Yiwei (China Intercontinental Press & New World Press, 2017)
This book explains the logic concerning globalization, civilization, strategy, economy, politics and diplomacy in an in-depth yet understandable way, and reveals the Chinese wisdom and global wisdom displayed by the Belt and Road Initiative. Based on the history of human civilization and reflection on globalization, it is a monograph on the Belt and Road Initiative after the publication of the same author's The Belt and Road Initiative: What Will China Offer the World in Its Rise one year ago.